PENGARUH PEMIKIRAN DAN GERAKAN POLITIK SYIAH IRAN DI INDONESIA - Gonda Yumitro (Dauliyah Journal of Islamic and International Affairs, 2017)
Based on its ideology and model of developed movement, Iranian Shia has beenintensely extending its ideology to various countries, including to Indonesia. Theexport of this ideology aims to create full power for Shia in the internationalworld. Through literature reviews methodology, it is found that the thought andmovement of Iranian Shia have influenced Indonesia significantly, especially bythe support of Iran. These influences can be seen by the increasing number offollowers, the development of education and publication activities, theinvolvement of Iran Shia cadres in Indonesian politics, and the developing ofunfair and unbalance cooperation between Indonesia and the Iranian government